Widening differences in Italian regional unemployment - Giorgio Brunello; Claudio Lupi; Patrizia Ordine (Fondazione Eni Enrico Mattei (FEEM), 1999)
Regional unemployment differentials among Italian regions have widened since the mid 1980s, especially between the leading Northern and Central areas and the underdeveloped South. We suggest that the following elements are important to explain the observed phenomenon: a) employment performance in the South has worsened considerably in the presence of sustained labour force growth; b) labour mobility from the South to the NC areas has sensibly declined with the reduction in earnings differentials and with the increase in social transfers per head; c) real wages in the South are not affected by local unemployment conditions but depend on the unemployment rate prevailing in the leading areas; d) the labour share increased particularly fast in the South during the 1970s, mainly as a consequence of the elimination of institutions that allowed the presence of significant wage differentials; e) a parsimonious description of the increase in regional unemployment differentials is that the Northern and Southern areas responded in an asymmetric way both to the increase in real social transfers per head and to the reduction in the real price of energy.
Keywords: J61; J64; 330; Regional unemployment; Labour mobility; Italy; Regionale Arbeitslosigkeit; Regionale Arbeitsmobilität; Italien